PSYCHOLOGICAL FACTORS OF STUDENTS’ INTERNAL MOTIVATION - Baranauskienė, Ingrida; Serdiuk, Liudmyla; Kovalenko, Alla (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article discusses the main approaches to research on an individual’s internal learning motivation. The factors and synergetic tendencies of learning motivation conditioned by value-semantic and personal characteristics are determined. The study purpose was to determine the factors of student’s internal academic motivation and the psychological foundations of their self-determination. The following psychological diagnostic techniques were used in the empirical study: the Morphological Test of Life Values developed by V.F. Sopov, L.V. Karpushina; V.V. Stolin’s and S.R. Pantileev’s Test-Questionnaire of Self-Attitudes; the techniques for learning motivation at universities proposed by T.I. Ilyina; T. Ehlers’ Mofivation of Success questionnaire. The sample consisted of 170 students of the second-forth academic years from the Faculty of Psychology, Taras Shevchenko National University of Kyiv. The obtained research results show that learning self-determination is ensured to the great extent by an individual’s meaningful life goals and perspectives, the internal control locus, personal autonomy. An important factor of an individual’s learning self-determination is the need for self-realization that actualizes the potential capabilities. It is shown that the conditions for students’ learning motivation formation and development are created and achieved thanks to the values of personal development, spiritual pleasure, creativity; a space of interpersonal interactions that provides moral support; personal traits such as self-esteem, self-acceptance, self-understanding and self-confidence. These conditions promote the development of professionally important qualities and values.